Learning to Read in the Heritage Language Supports Literacy Skills in the Majority Language Evidence from Greek-English Speaking Children - Papastefanou, Theodora (My University, 2024)
The first aim of the study was to investigate bilingual children’s performance in language and word-level reading (i.e., decoding) at two testing points, drawing comparisons between the heritage and majority languages (Greek-English) and between two age groups in the first four years of primary school. Secondly, we investigated whether contextual factors (i.e., quality and quantity of language exposure and input) can predict language and reading development. Additionally, we addressed whether there is a contribution to the children’s language scores in the heritage and majority language from Time 1 on decoding at Time 2 across languages. Forty children attending Years 1 and 3 of primary school were assessed in language and decoding skills and were then reassessed one year later in Years 2 and 4. The results showed that overall scores were higher in the majority than in the heritage language, but there were differences between the tasks in the developmental trajectory of the two languages. The results also showed more associations between contextual factors and the scores in the heritage language compared to the majority language, which suggests that the heritage language benefits from additional exposure and use. Finally, findings showed a concurrent and longitudinal relationship between phonological awareness and decoding skills, both within and between languages, supporting the orthographic transparency hypothesis.
Keywords: bilingualism; language